Bluecrowne - Milford, Kate (Milford, Kate. Greenglass House story., 2018)
Lucy Bluecrowne has only known life aboard her father's schooner, "Left-Handed Fate," where the crew has become like her family. So, when she is forced to live with her stepmother and half brother in a huge house on land, Lucy is horrified. It may be a safer and proper place for a twelve-year-old girl, but it is so boring, she knows she has to get back to "Left-Handed Fate." However, when two strangers take interest in her little brother's pyrotechnic skills, Lucy realizes she has to stay and figure out a mystery.